2004
DOI: 10.1016/j.cardiores.2004.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic depletion of cardiac myocyte STAT-3 abolishes classical preconditioning

Abstract: The depletion of functional STAT-3 does not modulate tolerance to ischemic injury in cardiomyocytes. This signaling molecule, however, is crucial for the ischemic and all the tested pharmacological preconditioning programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 42 publications
2
98
0
3
Order By: Relevance
“…6) The effects of the MLS-STAT3E transgene are observed with 45 min of ischemia, which is probably not sufficient time for isolated hearts to transcribe and translate STAT3-activated RNAs for the protective effects of the transgene to be due to its actions in the nucleus. In previous reports, where it has been shown that STAT3 protects against ischemia/reperfusion injury (4,40,41), it is likely that the actions of STAT3 are at least partially a result of its activation of nuclear genes. These protocols subject the hearts to 2-3 h of combinations of ischemia and reperfusion, which is sufficient time for STAT3-mediated induction and translation of nuclear encoded RNAs.…”
Section: Discussionmentioning
confidence: 97%
“…6) The effects of the MLS-STAT3E transgene are observed with 45 min of ischemia, which is probably not sufficient time for isolated hearts to transcribe and translate STAT3-activated RNAs for the protective effects of the transgene to be due to its actions in the nucleus. In previous reports, where it has been shown that STAT3 protects against ischemia/reperfusion injury (4,40,41), it is likely that the actions of STAT3 are at least partially a result of its activation of nuclear genes. These protocols subject the hearts to 2-3 h of combinations of ischemia and reperfusion, which is sufficient time for STAT3-mediated induction and translation of nuclear encoded RNAs.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, it was reported that cardioprotection associated with tumor necrosis factor-␣-induced preconditioning, as well as IPC, involves STAT3 activation during the early reperfusion phase (19). Cardiomyocytes genetically depleted of STAT3, while exhibiting degrees of viability similar to wild-type cardiomyocytes, have been shown to be nonresponsive to ischemic and pharmacological preconditioning, as have intact hearts (25). Furthermore, data were recently published (2) showing that cardioprotection stimulated by ischemic postconditioning is lost in STAT-3-deficient and aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that STAT1 modulates cardiac myocyte apoptosis after simulated ischemia and reperfusion [3,4]. In contrast, depletion of STAT-3 has been shown to abolish the cardioprotection afforded by preconditioning [19].…”
Section: Commentmentioning
confidence: 99%
“…Previous reports have shown that c-Jun interacts with STAT3 and enhances STAT3 DNA-binding [19][20][21][22][23]. In this report, we attempted to examine whether c-Jun interacts with STAT3 in our model by coimmunoprecipitation with anti-STAT3 antibodies followed by Western blot analysis with anti-c-Jun antibodies.…”
Section: Commentmentioning
confidence: 99%